An Analysis of English Classroom Interactions: Teacher Talk, Students’ Responses, and Students’ Opinions - Azizi, Meirita Rahmi; sisilia Setiawati Halimi (Universitas Cokroaminoto Palopo, 2024)
Teacher talk significantly influences classroom interactions since it holds dominance within a classroom. How teachers construct the classroom interaction will affect how well students receive and produce a language. Teacher talk can either offer positive or negative impacts depending on how it is applied. For this reason, it is critical to evaluate teachers as a reflection to improve the quality of learning. In this case, it is also necessary to delve into students’ responses and opinions during the classroom interaction. Therefore, this study aimed to examine modes and interactional features of a teacher talk based on the SETT framework and students’ responses and opinions to the teacher talk. The study employed a qualitative approach that combines qualitative descriptive research and discourse analysis. The findings showed three classroom modes and eight interactional features in the teacher talk. Another finding revealed that the most students responded to the teacher talk in specific and open-ended responses. Further finding showed that the students acknowledged the difficulties in comprehending the teacher talk and speaking in the English classroom. The factors contributing to these difficulties are linguistic and psychological factors. Thus, adjusting teachers’ language based on student language ability and establishing a convenient classroom environment should be considered